Fading Away: Technological Decline in Canadian Aviation - Cronin, Marionne (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2009)
AbstractWhen Western Canada Airways began flying its pioneering air route down the Mackenzie Valley in 1929, it did so with a fleet comprised entirely of Fokker Super Universal aircraft. By the end of 1933, however, the airline had declared the Super Universals obsolete, replacing them with other aircraft models. In only four years, the Fokker Super Universal had gone from state of the art to obsolescent. Exploring Western Canada Airways' decision to replace the Supers, this paper offers insight into the nature of obsolescence, demonstrating that the aircraft did not achieve this status because of technical changes or dramatic technical breakthroughs in the design of other aircraft. Instead, the Super Universal became obsolete because of changes in its use-context. The rise of the Great Bear Lake mineral rush, the introduction of new sorts of aircraft into the region, increased competition, and changing passenger expectations all encouraged Western Canada Airways' management to re-evaluate their definition of what constituted a superior technology within the context of the Mackenzie Valley. While conditions in 1929 made the Super Universal the best possible choice, by the end of 1933 those circumstances had changed such that the Super was now obsolete. By tracing this episode in Canadian aviation history, this paper will explore the contextual dimensions of obsolescence and the role of historical circumstances in effecting technological decline.